Information Needs of Prisoners and Adequacy of Information Resources in Prison Libraries in Anambra State, Nigeria - Udem, Obiora Kingsley; Emereonwu, Oluoma Miracle; Nwadibe, Chisom Marycynthia (International Journal of Knowledge Content Development & Technology, 2024)
This study investigated the information needs of prisoners and the adequacy of information resources in prison libraries in Anambra State, Nigeria. Two research questions guided the study. The population of the study was 1781 inmates in prisons in Anambra State. The sample size of 327 was selected using Taro Yamane’s formula and proportionate stratified sampling techniques. Two instruments titled the Information Needs of Prisoners Questionnaire and the Adequacy of Information Resources Checklist were used for data collection. The instruments were validated by three experienced lecturers. One in the department of Educational Foundations (Measurement and Evaluation Unit) and two in the Department of Library and Information Science, all at Nnamdi Azikiwe University, Awka. Cronbach's alpha was used to determine the internal consistency of the questionnaire items, with a value of 0.79. The researchers administered the questionnaires with the help of four research assistants (correctional officers). Out of 327 questionnaires administered, 314 were successfully retrieved. The percentage return rate of distributed questionnaires is 96%. Data collected were analyzed using descriptive statistics of the mean; also, the International Federation of Library Association (IFLA) guideline for library services to prisoners was also used as a yardstick for the measurement of adequacy. The results from the data analysis indicated that prisoners have diverse information needs that, when met, would help them during their stay in prison as well as when they are eventually released; these needs include legal information, information on prison rules, financial information, and others. While there were few information resources found to be adequate, the inadequacy of most of the listed information resources is recorded in prison libraries in Anambra State, Nigeria. It is therefore recommended that information resources be made adequately available for prisoners in relation to their information needs.